CD8(+) Lymphocytes Suppress Human Immunodeficiency Virus 1 Replication by Secreting Type I Interferons - Killian, M. Scott (Mary Ann Liebert, Inc., 2013)
CD8(+) cells can suppress human immunodeficiency virus 1 (HIV-1) replication by releasing soluble factors. In 26 years of intensive research efforts, the identity of the major CD8(+) cell antiviral factor has remained elusive. To investigate the mechanism for this antiviral immune response, we performed gene expression analyses on primary CD4(+) cells that were exposed to HIV-suppressing CD8(+) cells or CD8(+) cell-conditioned medium having HIV-suppressing activity. These experiments revealed increased levels of multiple genes stimulated by type I interferons (IFN; eg, IFN-α and IFN-β). Further evaluation revealed that primary CD8(+) cells, particularly those from elite controllers and other asymptomatic HIV-1-infected individuals, secrete IFN, and this response directly contributes to the in vitro suppression of HIV replication in CD4(+) cells. This novel immune response, likely mediated by memory CD8(+) T cells, may play an important role in a wide variety of viral infections, cancers, and autoimmune diseases.